Different kinetics of humoral response against individual antigens in the ovine model of Toxoplasma gondii infection and its pathological association - Formigo, Paula; Gual, Ignacio; Cantón, Germán J.; Mendoza Morales, Luisa F.; Sosa, Emiliano; Soto Cabrera, Agustina; Scioli, Valeria; Morsella, Claudia; Sander, Valeria A.; Moore, Dadin P.; Angel, Sergio O.; Campero, Lucía M.; et al. (Frontiers in Immunology, 2025)
BackgroundToxoplasma gondii is a globally distributed protozoan parasite with major implications for human and animal health. In sheep, infection can cause reproductive failure and represents an important source of zoonotic transmission through contaminated meat. While cell-mediated immunity is the main protective mechanism, the contribution of humoral responses, particularly against individual recombinant antigens (rAGs), remains poorly characterized in ovine toxoplasmosis.MethodsWe analyzed the humoral response of lambs experimentally infected with two reference strains of T. gondii (RH and Me49) using different inoculation doses. Recombinant antigens rGra4Gra7, rGra8, rRop2, rCST9, and rBCLA were tested by IgG-ELISA to evaluate their kinetics during infection. Histopathological analyses of brain tissues were performed to assess lesion severity and cyst presence. Additionally, sera from naturally infected sheep were evaluated to test diagnostic performance.ResultsAn early IgG response against rGra4Gra7 and rGra8 was detected, consistent with markers of acute infections. Anti-rBCLA, rRop2, and rCST9 IgG responses were associated with the chronic phase and correlated with cyst burden. Notably, stronger anti-rGra4Gra7 IgG responses tended to associate with lower lesion scores, suggesting a potential protective role. In naturally infected sheep, IgG-ELISA against rGra4Gra7 and rGra8 demonstrated the highest diagnostic performance, outperforming total lysate antigen (TLA)-based assays.ConclusionOur findings highlight distinct kinetics of specific antibody responses against selected T. gondii antigens in sheep, suggesting their value as markers of infection stage and pathology. rGra4Gra7 and rGra8 appear particularly promising both as diagnostic candidates and for exploring mechanisms of humoral modulation in ovine toxoplasmosis.